Juridical Comparison of the Mechanisms of Abolition and Amnesty in the Legal Systems of Russia and Indonesia - Hidayatulloh, Hanip; Saputra, M Reza (CV. Era Digital Nusantara, 2025)
The mechanisms of amnesty and abolition in the Indonesian and Russian legal systems serve similar objectives granting pardon or terminating criminal proceedings yet differ in scope and procedure. In Indonesia, amnesty extinguishes criminal legal consequences while preserving the conviction record, whereas abolition terminates prosecution and expunges all charges from inception. Under Article 14 of the 1945 Constitution, the President may propose amnesty or abolition subject to the approval of the House of Representatives (DPR). In contrast, Article 89 of the Russian Constitution vests in the President the individual prerogative to grant pardon without requiring legislative consent. This comparative qualitative study employs data triangulation and an audit trail to ensure the validity, reliability, and transparency of its findings. The study’s results indicate that in Indonesia, the 2025 instances of amnesty for political figures and abolition for former ministers exemplify the politicization of clemency processes, characterized by minimal victim participation and absence of objective criteria. Conversely, in Russia, the standard pardon procedure mandates an individual’s petition and acknowledgment of guilt, yet the practice of recruiting prisoners into military service under promises of clemency raises ethical and security concerns. Both systems vest broad interpretative discretion in the executive, heightening the risk of arbitrariness. Recommended reforms include the enactment of objective clemency criteria and increased procedural transparency in both jurisdictions, alongside integration of restorative justice principles such as mandatory acknowledgment of guilt, victim involvement, and public oversight to enhance accountability, promote restorative justice, and mitigate executive abuse of power.